2012
DOI: 10.1186/1476-072x-11-30
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns in the association between regional socio-economic context and dental caries experience according to gender and age: A multilevel study in Korean adults

Abstract: BackgroundLittle is known about the effects of socio-environmental factors on dental caries in different demographic situations in Asian populations. We investigated whether the nature of the association between regional socio-economic context and dental caries experience differed according to gender and age groups in Korean adults.MethodsWe obtained a linked data set containing individual information from the 2000 Korean National Oral Health Survey and regional information from the “Major statistical indices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
4
9
0
Order By: Relevance
“…Ultimately, this exercise showed that the interpretation of the prevalence of dental indicators of oral health in the past requires a greater emphasis on biocultural and environmental contexts of the populations under study. While this argument toward a better inclusion of local factors is not new and has been explored by other researchers (Lukacs 2011;Lee et al 2012;Russell et al 2013), our study illustrates the worldwide pattern of overlap between the prevalences of dental stress markers. Although categorical lifestyle patterns may sometimes be inferred from skeletal and dental remains, we join recent colleagues (e.g., Martin, Burr, and Sharkey 2013;Temple and Goodman 2014) in emphasizing that such conclusions require a deeper understanding of the biocultural context of the groups, since the variance in the prevalence of markers between groups is not well partitioned according to the subsistence or even climate differences among them.…”
Section: Discussionsupporting
confidence: 52%
“…Ultimately, this exercise showed that the interpretation of the prevalence of dental indicators of oral health in the past requires a greater emphasis on biocultural and environmental contexts of the populations under study. While this argument toward a better inclusion of local factors is not new and has been explored by other researchers (Lukacs 2011;Lee et al 2012;Russell et al 2013), our study illustrates the worldwide pattern of overlap between the prevalences of dental stress markers. Although categorical lifestyle patterns may sometimes be inferred from skeletal and dental remains, we join recent colleagues (e.g., Martin, Burr, and Sharkey 2013;Temple and Goodman 2014) in emphasizing that such conclusions require a deeper understanding of the biocultural context of the groups, since the variance in the prevalence of markers between groups is not well partitioned according to the subsistence or even climate differences among them.…”
Section: Discussionsupporting
confidence: 52%
“…In the case of the other group under study, they were organised in clubs for older adults, in which most of the participants are women. Regardless of the gender differences in the participants in this study, it has been reported that women have a higher caries experience compared with men, as pointed out above. This situation may make women more prone to have an interest in participating in this type of study.…”
Section: Discussionmentioning
confidence: 64%
“…All of the studies were published between 1975 and 2016 [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Twenty new studies were included in this update [26,27,28,29,31,38,39,40,44,45,…”
Section: Resultsmentioning
confidence: 99%
“…Twenty new studies were included in this update [26,27,28,29,31,38,39,40,44,45,47,49,50,53,59,61,66,67,79,81]. The language was predominantly English (96.7%).…”
Section: Resultsmentioning
confidence: 99%